The diversity of the intestinal microbiota in patients with alcohol use disorder and its relationship to alcohol consumption and cognition - Du, Yishan; Li, Lin; Gong, Chengcheng; Li, Ting; Xia, Yan (Frontiers in Psychiatry, 2022)
Alcohol use disorder (AUD) has evolved into a severe social and medical issue. However, the exact environmental factors triggering AUD pathophysiology remain unknown. A growing body of research has shown that environmental elements can affect the brain via the microbiota-gut-brain axis. We employed 16S rRNA gene sequencing technology to investigate the composition and diversity of intestinal microbiota in 32 AUD males and 35 healthy controls (HCs), as well as its relationship on cognitive function. Our findings showed that the alpha diversity indices in AUDs were much lower than HCs. The abundances of Faecalibacterium, Gemmiger, Lachnospiracea_incertae_sedis, Megamonas and Escherichia were significantly different between AUD and HC groups and could be used as a basis for judging whether excessive drinking. The abundances of Faecalibacterium, Gemmiger, Escherichia and Fusobacterium can be used to judge the cognitive function of the population. These data suggested that the gut dysbiosis in AUD patients, and some specific microbiota were considered to be related to alcohol intake and cognitive function. This study provides important information for further study of the pathogenesis of AUD from the perspective of intestinal microbiota.